2019
DOI: 10.1186/s12879-019-3984-5
|View full text |Cite
|
Sign up to set email alerts
|

“Sickenin’ in the rain” – increased risk of gastrointestinal and respiratory infections after urban pluvial flooding in a population-based cross-sectional study in the Netherlands

Abstract: Background Climate change is expected to increase the chance of extreme rainfall events in the Northern Hemisphere and herewith, there is an increased chance of urban pluvial flooding. Urban pluvial flooding often consists of street flooding and/or flooding of combined sewerage systems, leading to contamination of the floodwater with several gastrointestinal and/or respiratory pathogens. An increase in flooding events therefore pose a health risk to those exposed to urban floodwater. We studied th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(29 citation statements)
references
References 18 publications
0
27
2
Order By: Relevance
“…Notwithstanding the strict methodology of this case-crossover study, including climatological and air pollutants, temperature, relative humidity and barometric pressure in the analysis as potential confounders, the authors recognise that further studies are required to clarify what could be the role of indoor crowding in this association [49]. More recently, a cross-sectional survey in 60 Dutch locations with reported flooding did not find a significant association between the exposure to pluvial floodwater and acute respiratory infections in children (OR = 1.6 (95% CI: 0.6, 4.0)) [50].…”
Section: Extreme Weather Eventsmentioning
confidence: 92%
“…Notwithstanding the strict methodology of this case-crossover study, including climatological and air pollutants, temperature, relative humidity and barometric pressure in the analysis as potential confounders, the authors recognise that further studies are required to clarify what could be the role of indoor crowding in this association [49]. More recently, a cross-sectional survey in 60 Dutch locations with reported flooding did not find a significant association between the exposure to pluvial floodwater and acute respiratory infections in children (OR = 1.6 (95% CI: 0.6, 4.0)) [50].…”
Section: Extreme Weather Eventsmentioning
confidence: 92%
“…The authors of that study suggested that the tsunami increased the risk of pneumonia death. Regarding ooding-related disasters, there are some reports of increases in the occurrence of acute respiratory infections [2][3][4]. These reports included patients who were outpatients and had symptoms but had not been diagnosed with pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…Regarding the aetiology of pneumonia, the rate of Haemophilus in uenzae infection was signi cantly higher after tsunami and earthquake disasters [7]. Both contact with oodwaters and post-ooding cleaning were reported to increase the risk of respiratory infections [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous reports demonstrated that acute respiratory infections are a major cause of disease after hydrologic events such as tropical cyclones, typhoons, and other heavy rainfall-related events [2][3][4][5][6], and numbers of both outpatients and inpatients with pneumonia increase after such disasters [7,8].…”
Section: Introductionmentioning
confidence: 99%